2018
DOI: 10.1016/j.jss.2018.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Impaired growth outcomes in children with congenital colorectal diseases

Abstract: Patients born with CHARM anomalies are at risk for impaired growth. Furthermore study is warranted to identify modifiable risk factors contributing to this impairment. Longitudinal follow-up should include interventions to mitigate these risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…However, Veras et al demonstrated that children with colorectal diseases, including HD, with public insurance had a higher risk of impaired growth compared with patients with private insurance. 30 Further, there is data showing that payer status Further, our study found no significant association between preoperative HAEC and postoperative HAEC, which is contradictory to other reports. 8,10 This discrepancy might be explained by the lack of a consensus definition of HAEC.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Veras et al demonstrated that children with colorectal diseases, including HD, with public insurance had a higher risk of impaired growth compared with patients with private insurance. 30 Further, there is data showing that payer status Further, our study found no significant association between preoperative HAEC and postoperative HAEC, which is contradictory to other reports. 8,10 This discrepancy might be explained by the lack of a consensus definition of HAEC.…”
Section: Discussioncontrasting
confidence: 99%
“…Recommendations for long-term follow-up (Table 6) Structured follow-up to adulthood, including transition of care is indicated in HSCR [62][63][64][65][66]. As bowel dysfunction is most common during the first few years after surgery [23], patients should be monitored more closely for the early detection of problems, including defective continence, enterocolitis and late complications.…”
Section: Level Of Evidence III Strength Of Recommendation: Strong Fomentioning
confidence: 99%
“…A low weight for age (underweight) is a composite indicator and can reflect both stunting and wasting and therefore difficult to interpret [6]. In this study the above indices showed significant nutritional deficiencies in subjects with colonic stomas.…”
Section: Discussionmentioning
confidence: 63%
“…The results were expressed as Z scores which denoted the number of standard deviations from the mean. Children with scores below -2 standard deviations (< -2 SD) were considered as having nutritional deficits [6]. In all subjects the weights and heights/ lengths were taken by the scale from Measuretek® which was calibrated to an accuracy of 0.01 kgs and 0.1 cm (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation